Impact of dapagliflozin, an SGLT2 inhibitor, on serum levels of soluble dipeptidyl peptidase‐4 in patients with type 2 diabetes and non‐alcoholic fatty liver disease. Issue 5 (1st April 2019) - Aso, Yoshimasa; Kato, Kanako; Sakurai, Shintaro; Kishi, Haruka; Shimizu, Masanori; Jojima, Teruo; Iijima, Toshie; Maejima, Yuko; Shimomura, Kenju; Usui, Isao
Abstract: Aims: Soluble dipeptidyl peptidase‐4 (sDPP‐4) is secreted by hepatocytes and induces adipose tissue inflammation and insulin resistance. Sodium‐glucose co‐transporter‐2 (SGLT2) inhibitors can improve hepatic steatosis by inhibiting hepatic de novo lipogenesis. We investigated the effects of dapagliflozin (an SGLT2 inhibitor) on serum levels of sDPP‐4 in patients with type 2 diabetes and non‐alcoholic fatty liver disease (NAFLD). Methods: Fifty‐seven patients with type 2 diabetes and NAFLD were randomized to a dapagliflozin group (5 mg/d for 24 weeks) (n = 33) or the control group (n = 24). Serum levels of sDPP‐4 were measured with a commercial ELISA kit. Visceral adipose tissue (VAT) and subcutaneous adipose tissue (SAT) areas were measured by dual bioelectrical impedance analysis. Results: In a total of 57 patients, baseline serum sDPP‐4 was positively correlated with aspartate aminotransferase (AST), alanine aminotransferase (ALT), γ‐glutamyl transferase (GGT) and HOMA‐IR Both VAT and SAT areas decreased significantly in the dapagliflozin group alone. Liver enzymes were decreased at 24 weeks in the dapagliflozin group, but were unchanged in the control group. Although both groups showed significant reduction of serum sDPP‐4 after 24 weeks of treatment, the magnitude of decrease was significantly larger in the dapagliflozin group. Changes in liver enzymes during treatment with dapagliflozin were positively correlated with the change in serum sDPP‐4, but not with changes in VAT volume or HbA1c. Conclusions: Improvement of liver dysfunction after treatment with dapagliflozin was associated with a decrease in serum sDPP‐4, suggesting that reduction of serum sDPP‐4 by SGLT2 inhibitors may be a therapeutic strategy for NAFLD/NASH in patients with type 2 diabetes that is independent of glucose lowering or weight loss.